Fiscal Sovereignty vs. Coordination: The Struggle for Equality in Tax Regulation - Radvan, Michal (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
This chapter primarily aims to find the relationship between the cooperation and harmonisation tendencies of the EU in the area of taxation, as well as the competition between the tax systems of individual EU Member States. The request for unanimous consent in tax harmonisation in the area of direct taxes regulation is also an issue to be investigated. To achieve these aims, the chapter defines basic terms such as tax law and tax itself. Subsequently, the role and position of the tax law in the EU law are analysed and specified, and the essential terms ‘tax sovereignty’ and ‘tax harmonisation’ are defined. The chapter investigates the limits of taxation at the EU level and national levels in the EU Member States according to the Treaty on European Union and the Treaty on the Functioning of the European Union. Specific parts of the chapter focus on direct and indirect taxes. These parts analyse the EU politics published on the EU website and describe the EU law dealing with individual types of taxes by considering selected national specifics in the legal regulation of the EU Member States. The conclusions state that the ideal path is somewhere in the middle of tax harmonisation and tax sovereignty: tax issues should never become a coordinated policy at the EU level, and the EU’s task should be to prohibit tax discrimination, i.e., tax neutrality, to fight against harmful tax competition and tax evasion, and to promote greater cooperation between tax administrations in ensuring control and combating fraud.